al-‘Anāṣīru ad-Dākhiliyyatu fī “al-Māl wa al-ḥub” Fi Qiṣṣah al-Qaṣīrah al-Muḍīl - Hudzaifi, Ahmad Dicka (Middle Eastern Culture & Religion Issues, 2022)
This study aims to reveal the intrinsic elements short story " Al-Mālu wa al-Ḥubbu " in the anthology al-Mudīl by Saīd ‘Arafah and the relation among them. The story applied in this research is structural theory with structural analysis methods. The analyzed elements are character, plot, setting, theme, title, and point of view. Based on the analysis, the main character is Nasya’at. Meanwhile the additional figures in this short story are Faruq, Ridwan Barakat, Zubaidah, Abu Dahab al-Jablawy, the wife of Nasya’at, Doctor Shafwat and Syamandi. The plot in this short story is a straight line. The setting of the place in this short story are the palace, school, teacher’s room, hospital, and the directorate of security. The setting of time in this short story are after sunset, evening, morning, and early morning. The setting of social in this story is the social setting of society around the palace. The title of the short story " Al-Mālu wa al-Ḥubbu " refers to the themf of the story. The point of view used in this short story is a third person perspective-unlimited. The theme in this short story is ’’wealth and love which is taken on a good path will bring benefits, but the one which used for a bad path will bring destruction’. In this short story, the main character is portrayed as a good and generous doctor who is his belief being abused by other characters in the short story. This short story has a relationship between the elements, they are themes with characters, themes with plot, themes with titles, and themes with background. Each intrinsic element in this short story has and interrelation in producing the meaning of the story.